الإختصاص السلبي للمشرع في الجزائر - عنان أمال (University Of Eloued جامعة الوادي, 2020)
تطرقت هذه الدراسة إلى الكشف عن جوانب مهمة لموضوع عدم الاختصاص السلبي للمشرع - الذي اصطلح عليه بالإغفال التشريعي أو الغموض التشريعي وتحديد أنجع الحلول له المعتمدة في الجزائر ، والتعرف على بعض التشريعات التي عالجت هذا الموضوع، ومحاولة الوقوف على الانعكاسات غير المحمودة على الحقوق والحريات الناجمة عنه من بينها مشكلة الأمن القانوني، ومن خلالها التركيز على موقف المشرع الجزائري الذي كان له دور بارز في إيجاد الحلول من خلال تكريس النصوص الدستورية والتشريعية ذات العلاقة بالموضوع، إضافة لذلك حاولنا تقييم دوره وكذا دور القضاء الجزائري فيما قدمه من اجتهادات كالتحفظات التفسيرية بتصحيح بعض من الإغفال التشريعي، حيث ختمت الدراسة في الأخير بتقديم جملة من المقترحات تهدف لإيقاف مشكلة عدم الاختصاص السلبي واحترام قواعد توزيع الاختصاص ليتحقق أخيرا أهم الأدوار الذي وجدت من أجله التشريعات ضمان الحقوق والحريات. Abstracts This study has focused on revealing important aspects of the issue of negative legislative incompetence - which has been characterized as legislative omission or legislative ambiguity and also on identifying the most effective solutions adopted for it in Algeria, on the identification of certain legislations which deal with this question, while trying to identify its undesirable repercussions on the rights and freedoms which flow from it, including the problem of legal certainty, and also to concentrate on the position of the Algerian legislator, who had a leading role in the search for solutions through the consecration of constitutional and legislative texts relating to this subject. In addition, we have tried to assess its role, as well as the role of Algerian justice, in its case law, such as interpretative reservations, by correcting certain legislative gaps. Finally, the study was concluded with a presentation of a number of proposals aimed at curbing the problem of negative incompetence and respecting the rules of distribution of competences, in order to finally achieve the most important role for which legislation has been found, which is to guarantee the rights and freedoms.
أطروحة
Keywords: الإختصاص السلبي; الإغفال التشريعي; المشرع; الدستور; Negative jurisdiction; legislative omission; legislator; constitution